UPAYA PENINGKATAN PRESTASI SISWA DI SMP NEGERI 7 SAWALUNTO - Sudirman, Sudirman; Hendriani, Suswati (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2022)
The main problem in this writing is the Efforts to Improve Student Achievement at Sawalunto 7 Public Middle School. the subject of discussion is how to improve student achievement. And how are the actions taken by teachers and parents towards students in increasing student achievement. The type of research that the writer did was field research which is a qualitative description. Data collection techniques that the authors use are through observation, interviews, and documentation. The validity of the data used is triangulation. Learning achievement is something that cannot be separated from learning activities, because learning activities are a process, while learning achievement is the output of the learning process. Fulfillment of learning facilities stated by Thamrin Nasution